Implementasi Sistem Akuisisi Data Sensor Pertanian Menggunakan Protokol Komunikasi LoRa - Richad Gilang Wisduanto; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Periodic monitoring of agricultural environmental condition is needed to growth the plant will be better, so it will improve the quality and quantity of agricultural products. The way of monitor environmental conditions periodically is an acquisition data system. The system requires minimum of two nodes, namely sensor nodes and gateways. Sensor node has function to put the data from the sensor and transmit it to the gateway, while the gateway receives the data and store it. Beside that a communication protocol is needed to connect both of nodes and to transmit the data wirelessly to remote monitoring, which one of it is LoRa. LoRa is a technology which has a wide range with low battery consumption, so it is suitable for monitoring agriculture in Indonesia, which is known as an agricultural country because of the wide area of agricultural land. There are two tests had been done, that are functional testing and performance testing. In the functional testing, the system can run properly where the system can put the till save it. The performance testing was hold to see the performance of the LoRa HopeRF-RFM9x module based on packet loss and delay with the influence of distance, packet size, and interval of delivery time. The result of the performance is the HopeRF-RFM9x module can transmit the packets well for 200, 300 and 400 meters.